Solve for k k-69=5k+3

Math
k-69=5k+3
Move all terms containing k to the left side of the equation.
Tap for more steps…
Subtract 5k from both sides of the equation.
k-69-5k=3
Subtract 5k from k.
-4k-69=3
-4k-69=3
Move all terms not containing k to the right side of the equation.
Tap for more steps…
Add 69 to both sides of the equation.
-4k=3+69
Add 3 and 69.
-4k=72
-4k=72
Divide each term by -4 and simplify.
Tap for more steps…
Divide each term in -4k=72 by -4.
-4k-4=72-4
Cancel the common factor of -4.
Tap for more steps…
Cancel the common factor.
-4k-4=72-4
Divide k by 1.
k=72-4
k=72-4
Divide 72 by -4.
k=-18
k=-18
Solve for k k-69=5k+3

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top